A pilot study on the nutraceutical properties of the Citrus hybrid Tacle® as a dietary source of polyphenols for supplementation in metabolic disorders. (January 2019) - Casacchia, Teresa; Occhiuzzi, Maria Antonietta; Grande, Fedora; Rizzuti, Bruno; Granieri, Maria Concetta; Rocca, Carmine; Gattuso, Alfonsina; Garofalo, Antonio; Angelone, Tommaso; Statti, Giancarlo
Graphical abstract: Highlights: Extracts of the Citrus Tacle have been investigated for their polyphenol content. Nutraceutical properties were assessed by antienzymatic in vitro assays. Naringenin and hesperetin were docked into amylase and lipase active sites. Effects on anthropometric parameters have been assessed in vivo on rats. Abstract: Tacle® is a citrus variety obtained from the crossbreeding of Clementine and Tarocco tetraploids. This new fruit recently gained an increasing interest due to its commercial value and nutraceutical properties. A high content in polyphenols confers to its extracts a protective activity against oxidative agents involved in several degenerative disorders. In this study, we investigated the antioxidant potential of Tacle and its inhibitory activity against human amilase and lipase in vitro . These particular features could be ascribed to the relevant content in naringin and hesperidin glycosides and the corresponding aglycones have been in silico demonstrated able to bind the active site of both enzymes. The overall results showed an enhanced nutraceutical profile of Tacle with respect to citrus parents, suggesting that a dietary enrichment with its extracts could be useful in the complementary treatment of metabolic disorders such as obesity and diabetes, as assessed by in vivo experiments on rats.